Actual patient position versus safety models: Specific Absorption Rate implications of initial head position for Ultrahigh Field Magnetic Resonance Imaging. (12th December 2022) - Kopanoglu, Emre
Abstract: Specific absorption rate (SAR) relates power absorption to tissue heating, and therefore is used as a safety constraint in magnetic resonance imaging (MRI). This study investigates the implications of initial head positioning on local and whole‐head SAR. A virtual body model was simulated at 161 positions inside an eight‐channel parallel‐transmit (pTx) array. On‐axis displacements and rotations of up to 20 mm/degrees and off‐axis axial/coronal translations were investigated. Single‐channel, radiofrequency (RF) shimming (i.e., single‐spoke pTx) and multispoke pTx pulses were designed for seven axial, five coronal and five sagittal slices at each position (the slices were consistent across all positions). Whole‐head and local SAR were calculated using safety models consisting of a single (centred) body position, multiple representative positions and all simulated body positions. Positional mismatches between safety models and actual positions cause SAR underestimation. For axial imaging, the actual peak local SAR was up to 4.2‐fold higher for both single‐channel and 5‐spoke pTx, 3.5‐fold higher for 3‐/4‐spoke pTx, and 2‐fold higher for RF shimming and 2‐spoke pTx, compared with that calculated using the centred body position. For sagittal and coronal imaging, the underestimation of peak local SAR was up to 5.2‐fold and 3.8‐fold, respectively. Using all body positions to estimate SAR prevented SAR underestimation but yielded up to 11‐fold SAR overestimation for RF shimming. Local SAR of single‐channel and pTx multispoke pulses showed considerable dependence on the initial patient position. RF shimming yielded much lower sensitivity to positional mismatches for axial imaging but not for sagittal and coronal imaging. This was deemed attributable to the higher degrees‐of‐freedom of control offered by the investigated coil array for axial imaging. Whole‐head SAR is less sensitive to positional mismatches compared with local SAR. Nevertheless, whole‐head SAR increased by up to 80% for sagittal imaging. Local and whole‐head SAR were observed to be more sensitive to positional mismatches in the axial plane, because of larger variations in coil‐tissue proximity. Using all possible body positions in the safety model may become substantially over‐conservative and limit imaging performance, especially for the RF shimming mode for axial imaging. Abstract : A positional mismatch between the actual head position and that of the safety model leads to underestimation of the specific absorption rate, by up to 4.2‐fold for peak local SAR and 1.4‐fold for whole‐head SAR. RF shimming offers reduced sensitivity to positional variations compared with single‐channel transmit and parallel transmit, for axial imaging.